Workplace Subjective Alienation and Individuals’ well-being - Adibifar, Karam; Monson, Melissa (Journal of Economic Development, Environment and People, 2020)
There are many sociological studies that have consistently demonstrated the importance of workplace alienation and its association with human health. However, nearly all research has focused on the objective dimension of alienation, overlooking the significance and in-depth understanding of subjective or covert forms of alienation. The purpose of this study is to explore the role and impact of subjective alienation on the mental and physical well-being of individuals, utilizing secondary analysis of data. The spillover effect of this type of alienation in relation to workplace behavior can significantly impact many aspects of people’s lives. Generally, alienation is the feeling of being disconnected and often occurs in the presence of, or presumed differentiation in social status. It lies in discrepancy and contradiction between subjective emotion and objective sensation; it is an inauthentic human relationship. This study finds that as a subtle form of bullying, covert alienation can produce significant levels of stress, which has countless consequences including emotional, financial, and physical problems. The findings also suggest that a lack of support in helping an alienated individual results in further alienation, leading to deviant behavior. Overall, this study may be helpful to organizations in recognizing maladaptive behaviors that might cause workplace alienation. Moreover, this study can be additional avenue to literature reviews, specifically in the area of subjective alienation.